Stem-Cell-Derived Circulating Progenitors Dysfunction in Behçet's Syndrome Patients Correlates With Oxidative Stress - Emmi, Giacomo; Mannucci, Amanda; Argento, Flavia Rita; Silvestri, Elena; Vaglio, Augusto; Bettiol, Alessandra; Fanelli, Alessandra; Stefani, Laura; Taddei, Niccolò; Prisco, Domenico; Fiorillo, Claudia; Becatti, Matteo (Frontiers in Immunology, 2019)
Behçet’s syndrome (BS) is a systemic vasculitis considered as the prototype of a systemic inflammation-induced thrombotic condition whose pathogenesis cannot be explained just by coagulation abnormalities. Circulating hematopoietic progenitor cells (CPC), a population of rare, pre-differentiated adult stem cells originating in the bone marrow and capable of both self-renewal and multi-lineage differentiation, are mobilized in response to vascular injury and play a key role in tissue repair. In cardiovascular diseases low circulating CPC number and reduced CPC function have been observed. Oxidative stress may be one of the relevant culprits that accounts for the dysfunctional and numerically reduced CPC in cardiovascular diseases. However, the detailed mechanisms underlying CPC number reduction are unknown. On this background, the present study was designed to evaluate for the first time the possible relationship between CPC dysfunction and oxidative stress in BS patients. In BS patients we found signs of plasma oxidative stress and significantly lower CD34+/CD45-/dim and CD34+/CD45-/dim/CD133+ CPC levels. Importantly, in all the considered CPC subsets, significantly higher ROS levels with respect to controls were observed. Higher levels of caspase-3 activity in all the considered CPC population and a strong reduction in GSH content in CPC subpopulation from BS patients with respect to controls were also observed. Interestingly, in BS patients, ROS significantly correlated with CPC number and CPC caspase-3 activity and CPC GSH content significantly correlated with CPC number, in all CPC subsets. Collectively, the data here reported demonstrate for the first time that CPC from BS patients, show signs of oxidative stress and apoptosis and that a reduced CPC number is present in BS patients with respect to controls. Interestingly, we observed an inverse correlation between circulating CPC number and CPC ROS production, suggesting a possible toxic ROS effect on CPC in BS patients. The significant correlations between ROS production/GSH content and caspase-3 activity point out that oxidative stress can represent a determinant in the onset of apoptosis in CPC. These data support the hypothesis that oxidative stress-mediated CPC dysfunctioning may counteract their vascular repair actions thereby contributing to the pathogenesis and the progression of vascular disease.